Algae: A natural active material for biomedical applications. Issue 4 (23rd February 2021) - Zhong, Danni; Du, Zhen; Zhou, Min
Abstract: Tremendous opportunities exist for biomaterials in biomedical applications. Microalgae, as a kind of natural resources, have been recently used as novel biological materials, and have attracted a great deal of interest in this field. The unique morphological characteristics and easily functionalized surfaces of microalgae allow the attachment of diagnostic or therapeutic agents on their surface, making them promising candidates for the construction of novel biochemical probes, drug carriers or biomedical scaffolds. As a natural photosynthetic system with rich autofluorescent pigments, algae can improve local oxygen concentration by in situ oxygen production and perform biomedical imaging (fluorescence imaging and photoacoustic imaging), which have been widely studied in the diagnosis and therapies of hypoxia‐associated diseases such as solid tumors and wounds. This review offers a summary of the biological properties of microalgae as well as their recent developments in diagnostic and therapeutic applications in bioanalysis, tissue engineering, hypoxia‐associated tumor therapy and wound healing. This naturally abundant, low cost and biocompatible material offers algae‐based agents an exceptional potential for commercial and clinical practice. Abstract : Biomaterials are widely used in biomedical field due to their low toxicity, among which microalgae, as a natural material, have begun to attract great attention. The work of Zhong et al systematically has summarized the characteristics and classification of microalgae and emphatically introduced the biomedical application research based on microalgae in recent years.